2016
DOI: 10.4236/ojvm.2016.61003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Technology Adoption in Small Community Farmers in Relation to Reproductive Events in Tropical Cattle Raised under Dual Purpose Systems

Abstract: The impact of technology adoption among farmers in developing countries has been an issue difficult to measure and interpret. Hence, research to improve production has been centered in technology that possible is not adequate for this region. The present review aims to utilize subjects such as Genetics, Reproduction, Nutrition, Management and Animal Health as examples of research endeavors illustrating the scarcely bond existing between research and adoption of technology. A final section is an attempt to illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Most of the farmers with 6 to 7 family members showed a significant preference to AI whereas those with small families (up to 3 members) and those with very large families (with over 7 members) preferred to use natural service for breeding (p < 0.05). Our results are consistent with those of some workers (Howley et al, 2012;Dehinenet et al, 2014;Galina et al, 2016) who reported a positive relationship between family size and AI adoption. The results, however, contradict with other reports (Teferal, 2013) who reported that family size was negatively correlated with AI adoption.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Most of the farmers with 6 to 7 family members showed a significant preference to AI whereas those with small families (up to 3 members) and those with very large families (with over 7 members) preferred to use natural service for breeding (p < 0.05). Our results are consistent with those of some workers (Howley et al, 2012;Dehinenet et al, 2014;Galina et al, 2016) who reported a positive relationship between family size and AI adoption. The results, however, contradict with other reports (Teferal, 2013) who reported that family size was negatively correlated with AI adoption.…”
Section: Discussionsupporting
confidence: 83%
“…This could be possibly because of the costs involved in the movement of personnel and equipment for the AI procedure. Similar observations were also reported by other scholars (Teferal, 2013;Tebug et al, 2014;Galina et al, 2016;Rathod et al, 2017). Distance was related to increase in costs, which is essentially a hindrance for farmers to use AI.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations